2017
DOI: 10.1071/ah15241
|View full text |Cite
|
Sign up to set email alerts
|

Developing the rural health workforce to improve Australian Aboriginal and Torres Strait Islander health outcomes: a systematic review

Abstract: Objective. The aim of the present study was to identify evidence-based strategies in the literature for developing and maintaining a skilled and qualified rural and remote health workforce in Australia to better meet the health care needs of Australian Aboriginal and/or Torres Strait Islander (hereafter Aboriginal) people.Methods. A systematic search strategy was implemented using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and checklist. Exclusion and inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 30 publications
3
75
0
Order By: Relevance
“…A key factor that we believe impeded project success was staffing challenges, including high turnover (Table 4)—a well‐recognized problem in our setting28, 29 Solutions to rural health workforce shortages and turnover have been identified, including increased training and workplace support for Aboriginal people; strategies to develop professional development opportunities, peer support, and community connectedness for nonlocal staff; and placement of students to promote rural and remote career choices 30. Findings from our study suggest that greater effort is needed in implementing such strategies.…”
Section: Discussionmentioning
confidence: 99%
“…A key factor that we believe impeded project success was staffing challenges, including high turnover (Table 4)—a well‐recognized problem in our setting28, 29 Solutions to rural health workforce shortages and turnover have been identified, including increased training and workplace support for Aboriginal people; strategies to develop professional development opportunities, peer support, and community connectedness for nonlocal staff; and placement of students to promote rural and remote career choices 30. Findings from our study suggest that greater effort is needed in implementing such strategies.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of desire to work in Aboriginal health, studies only provided evidence of students’ intentions (Abuzar et al, ; Abuzar & Owen, ; Hart et al, ). A larger pool of evidence in the rural health context suggests that providing students with rural and remote placements in Aboriginal communities might contribute to the workforce over time (Gwynne & Lincoln, ). Additionally, a study comparing career choice of nursing students, who undertook either a rural or metropolitan clinical placement, found that significantly more students who undertook a rural placement (77%) intended to seek work rurally than those who had a metropolitan placement (42%) ( P < .0001) (Courtney, Edwards, Smith, & Finlayson, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with a growing body of literature articulating the difficulties faced by Aboriginal people in entering and remaining in the health workforce. These include, for example, difficulties with balancing family and community responsibilities, poor levels of secondary education, and a range of structural and systemic barriers within the AHP health profession [ 19 , 20 ]. One key systemic barrier identified is the mismatch between the amount of training received and the levels of responsibility and community expectations of AHPs [ 14 ].…”
Section: Discussionmentioning
confidence: 99%